Apparel, Black Culture and Négritude Movement: ethnographic data in the light of the Discursive Semiotics of shame and pride (Revista de Ensino em Artes, Moda e Design, 2026)
This article stems from a broader master’s dissertation aimed at understanding the meanings of apparel consumption within the Blackness Movement (or Négritude Movement). To achieve this, we employed theories of material culture, conducting an ethnography involving the Facebook profiles of 64 Black individuals engaged in the anti-racist struggle and the promotion of Black identity. As part of the results, we observed that the data are categorized into two narrative axes structured according to Discursive Semiotics theories regarding shame and pride. On one hand, participants communicate that a racist society instills shame in Black people for wearing apparel associated with Black culture, manipulating them to reject, abandon, and conceal such garments. On the other hand, participants demonstrate resistance to this manipulation by identifying with an ideal (perfect) image of Blackness and of pre-colonial African culture. Pride for this idealized image is manifested today through the adoption, maintenance, and exhibition of what we term “apparel of pride for the idealized Black/African culture,” which includes: a) turbans; b) dresses with African ethnic prints; c) men’s tunics, shirts and T-shirts with African ethnic prints; d) African ethnic prints in apparel in general; e) African fabrics produced in or imported from Africa; f) accessories with direct reference to Africa or Afro-culture; g) apparel with references to Egypt. This research is relevant for constructing a more pluralistic knowledge of apparel, providing a vast collection of images of clothing and accessories worn by Black people that intersect with their struggle against racism and in favor of Black identity.
Keywords: apparel; blackness; material culture; anti-racism